ARCHAEOLOGICAL WORKS IN THE LAND OF LĂPUȘ - Marta Ioana Moldoveanu; Paul Popa; Daniela Lucia Manea (Journal of Ancient History and Archaeology)
Over time many lands emerged across the Romanian territories where undeniable cultural characteristics stood the test of time. To some extent, the specific or general culture, habits and traditions which complete the Romanian cultural heritage were set apart by the various geographical areas and landforms. It is absolutely vital and imperative to unearth, preserve and promote the cultural values of each land, in particular of the Land of Lăpuș. Their diversity calls for more and unabated attention to how they have become an integral part of the dynamics of rural development and highlights the importance of such an environment and of its conservation against any changes which might erode the very cultural fabric of the areas.